Repurposing Antimalarials to Tackle the COVID-19 Pandemic - Krishna, Sanjeev (Trends Parasitol, 2021)
Artemisinin-based combination therapies (ACTs) have demonstrated in vitro inhibition of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Artemisinins have also shown anti-inflammatory effects, including inhibition of interleukin-6 (IL-6) that plays a key role in the development of severe coronavirus disease 2019 (COVID-19). There is now sufficient evidence for the effectiveness of ACTs, and in particular artesunate/pyronaridine, to support clinical studies for COVID-19 infections.